Strengthening Local Revenue Through Service Innovation: Digitalization, Human Resources, and Collaboration in Construction Testing Retribution - Septian Satria Erlangga Putra (Indonesian Journal for Entrepreneurial Review, 2025)
Local governments in Indonesia are under increasing pressure to strengthen Pendapatan Asli Daerah (PAD) as a foundation of fiscal independence under decentralization. While retributions are often treated as routine revenue instruments, their management reflects the broader capacity of local institutions to innovate and deliver quality services. This study examines the role of service innovation in enhancing PAD through construction testing retributions at the UPT Pengelolaan dan Pelayanan Perumahan dan Permukiman. Using a mixed-methods design, the research combines quantitative surveys of 100 service users with qualitative interviews of 12 stakeholders, including UPT staff, local government officials, contractors, and professional associations. Secondary data from regulations, financial reports, and PAD statistics (2019–2023) were also analyzed. Quantitative data were tested using Pearson correlation and regression analysis, while qualitative data were thematically coded to capture institutional strategies and challenges. Findings reveal that digitalization significantly improved efficiency, transparency, and user satisfaction, with 78% of respondents preferring online systems. Service quality was strongly correlated with compliance (r = 0.72, p < 0.05), underscoring the importance of professionalism and responsiveness. Human resources played a decisive role, as staff competence determined the effectiveness of technological adoption, yet irregular training and limited budgets remained constraints. Meanwhile, collaborative governance — particularly partnerships with associations and universities — expanded technical capacity and legitimacy, although such partnerships lacked institutionalization. This study contributes to the literature by linking fiscal decentralization with micro-level institutional practices, showing that local revenue generation depends not only on regulatory frameworks but also on frontline service innovation. Policy implications emphasize the need for investments in digital infrastructure, continuous staff development, and formalized collaboration to sustain innovation. By shifting the perspective from revenue extraction to revenue legitimacy, this study highlights how compliance can be built on trust, transparency, and credible service delivery.